2022
DOI: 10.3390/s22041395
|View full text |Cite
|
Sign up to set email alerts
|

A Survey of NOMA for VLC Systems: Research Challenges and Future Trends

Abstract: Visible light communication (VLC) has become a promising technology for high data rate communications and an attractive complementary to conventional radio frequency (RF) communication. VLC is a secure, energy efficient and cost-effective technology that exploits the existing infrastructure, particularly in indoor environments, for wireless data transmission. Nevertheless, the main limitation of developing high data rate VLC links is the narrow modulation bandwidth of light-emitting diodes (LEDs), which is in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 121 publications
(140 reference statements)
0
21
0
Order By: Relevance
“…Photodiodes are inexpensive and provide low complexity implementation for VLC as the modulation techniques are based on light intensity. In this case, achieving higher data rates is constrained to the response time of the photodiode [1][2][3]. On the other side, exploration of other light properties such as color has shown promising results in terms of better data rate, Refs.…”
Section: Introductionmentioning
confidence: 99%
“…Photodiodes are inexpensive and provide low complexity implementation for VLC as the modulation techniques are based on light intensity. In this case, achieving higher data rates is constrained to the response time of the photodiode [1][2][3]. On the other side, exploration of other light properties such as color has shown promising results in terms of better data rate, Refs.…”
Section: Introductionmentioning
confidence: 99%
“…In the two user PD-NOMA a single-level of SIC is used by the strong user to eliminate the signal of the weak user. Due to non-orthogonal nature of PD-NOMA the inter users' interference is maximum and it becomes worst if more numbers of users are involved [15,16]. Proper power allocation strategies can help to reduce such interference.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that NOMA can significantly improve spectral efficiency and network capacity in wireless communication systems [ 8 , 9 ]. More recently, various NOMA techniques have been investigated, applying grant-free multiple access [ 3 , 10 ], backscatter communication [ 11 ], reconfigurable intelligent surface (RIS) [ 12 , 13 ], relay-assisted network [ 14 ], unmanned aerial vehicle (UAV)-enabled network [ 15 ], visible light communication (VLC) [ 16 ], etc.…”
Section: Introductionmentioning
confidence: 99%